Behavioral Testing Design for Evaluation of Cognitive Disabilities. Issue 2 (23rd February 2022) - Riet, Fabrice; Mittelhaeuser, Christophe; Lux, Aline; Bour, Raphael; Selloum, Mohammed; Sorg, Tania; Herault, Yann; Meziane, Hamid
Abstract: Intellectual disabilities (ID) constitute a class of human neurodevelopmental diseases and are a major medical and socioeconomic problem owing to their high incidence and enormous burden to the families of those affected. In the past three decades, mutant mouse technologies have provided powerful tools for elucidating the pathophysiological mechanisms underlying behavioral and developmental alterations related to IDs and for addressing new therapeutic strategies, and major progress has been made revealing previously unidentified genes involved in ID. However, the pathological hallmarks of IDs are very heterogeneous in regard to both the functional deficits observed and the severity of the phenotype, even within the same mutation types. For this reason, an appropriate experimental design is required to reduce the risk of false negatives and positives in animal functional genomic studies. This experimental design should address functions important to evaluate, tests, and the appropriate workflow. Here, we propose an extensive behavioral screen with detailed protocols, which was successfully used in a systematic mouse functional genomic approach to gain pathway‐based insights into mechanisms leading to cognitive dysfunction in humans. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Assessment of circadian activity and ingestive behavior Basic Protocol 2 : Assessment of neurological reflexes and motor abilities using the grip and rotarod tests Basic Protocol 3 : Evaluation of anxiety‐related behavior using the elevated plus maze Basic Protocol 4 : Evaluation of recognition memory using the object recognition task Basic Protocol 5 : Evaluation of social behavior using the social recognition test Basic Protocol 6 : Evaluation of working memory using the Y‐maze spontaneous alternation test Basic Protocol 7 : Evaluation of emotional learning and memory using the fear conditioning test